2019
DOI: 10.1002/cche.10185
|View full text |Cite
|
Sign up to set email alerts
|

The effect of using water sumac (Rhus coriaria L.) extract on wheat pan bread quality characteristics

Abstract: Background and objectives Bread is a staple food that is widely consumed worldwide. The present study aimed to evaluate the use of sumac extract as a natural and functional improver on the quality attributes of wheat pan bread. Water sumac extracts were prepared at different sumac powder: water concentrations (w:v; 0.5%, 1%, 1.5%, 3%, and 5%) and then used in kneading of the dough and compared to the control dough kneaded with only water. Findings The rheological properties of the dough were measured using far… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Al-Marazeeq et al tested the effect of water sumac fruit extract on the production of wheat pan bread. They showed that sumac extract improved in concentration-dependent manner the quality characteristics of the pan bread [ 155 ]. The authors attributed these improvements to the extractable organic acids, polyphenols, tannins, and anthocyanins from sumac.…”
Section: Beneficial Effect Of Rhus Coriaria In mentioning
confidence: 99%
“…Al-Marazeeq et al tested the effect of water sumac fruit extract on the production of wheat pan bread. They showed that sumac extract improved in concentration-dependent manner the quality characteristics of the pan bread [ 155 ]. The authors attributed these improvements to the extractable organic acids, polyphenols, tannins, and anthocyanins from sumac.…”
Section: Beneficial Effect Of Rhus Coriaria In mentioning
confidence: 99%
“…In one research, when a specified amount of sumac flour was added to wheat bread, the phenolic and fiber content of the enriched bread was increased and the salt content was decreased because sumac provides a mild salty taste, however, sumac flour in wheat bread should not exceed 3 g/100 g for sensory acceptance [58]. The preparation of pan bread with 3% and 5% concentrations of water sumac extract enhances the acceptability of this type of bread, in addition to the improvement of its rheological properties and quality characteristics [59]. For that, sumac succeeded as being a natural food additive as it added a lot of improvements in the bakery industry.…”
Section: Application Of Sumac In Breadmentioning
confidence: 99%